COVID-19 online learning challenges: Kazakhstan secondary schools case study - Nurgaliyeva, S.; Bolatov, A.; Abildina, S.; Zeinolla, S.; Kurbonova, B.; Kyyakbayeva, U. (Frontiers in Education, 2024)
Background: The COVID-19 pandemic necessitated a rapid transition to online learning (OL) globally, posing significant challenges for educational systems. This study investigates the experiences of secondary school students in Kazakhstan, highlighting the adaptation processes, educational outcomes, and challenges faced during this shift. Methods: Data were collected through an online survey administered to 3,670 secondary school students across Kazakhstan, selected through convenience sampling. The survey comprised 21 questions using a combination of Likerttype scales and multiple-choice questions to capture students’ demographic details, satisfaction levels, perceived difficulties, and academic performance changes during OL. Data validation was ensured by cross-referencing responses, descriptive statistics, T-tests, ANOVA, correlation analysis, and regression were employed to analyze the data and identify factors influencing students’ attitudes toward OL and the associated challenges.
Keywords: attitude; challenges; COVID-19; online learning; perspectives; secondary school